SIGNIFICANCE OF DISCRIMINANT ANALYSIS FOR CLASSIFICATION AND TALENT IDENTIFICATION IN SPORTS – A THEMATIC REVIEW - Singh, Pankaj; Bisht, Sujay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Talent identification, crucial in sports, education, and employment, utilizes Multiple Discriminant Analysis (MDA) to assess various predictor variables for talent levels. MDA helps pinpoint factors correlated with success, such as physical attributes, skills, and psychological traits, aiding in tailored training and team selection. In sports, MDA serves to identify critical combinations of attributes, distinguish elite athletes, spot potential talent early, and tailor talent identification models to different sports. While widely used, MDA’s effectiveness across diverse sports disciplines remains underexplored, with gaps in understanding its applicability and reliability in different contexts. Further research is needed to determine how well MDA discriminates between athletes in sports with varied demands and to select appropriate variables for different sports. This review underscores the importance of MDA in talent identification and calls for more focused studies to enhance its application and effectiveness in sports contexts.